Maladaptive personality traits and the course of suicidal ideation in young adults with bipolar disorder: Cross‐sectional and prospective approaches. Issue 3 (31st August 2020) - Kudinova, Anastacia Y.; MacPherson, Heather A.; Musella, Katharine; Schettini, Elana; Gilbert, Anna C.; Jenkins, Gracie A.; Clark, Lee Anna; Dickstein, Daniel P.
Abstract: Background: Childhood‐onset bipolar disorder (BD) has considerable morbidity and mortality, including suicide. Many risk factors have been identified for suicidality, but the potential role of personality traits as assessed by a computer‐assisted self‐report measure remains unclear. Aims: To address this gap in knowledge, we tested relations between pathological‐range personality traits and suicidal ideation among young adults whose childhood‐onset BD was prospectively confirmed by enrollment in the Course and Outcome of Bipolar Youth study (COBY) as children ( n  = 45) and a newly enrolled group of typically developing controls (TDCs; n  = 52) both cross‐sectionally and longitudinally after 1.5 years of follow up. Materials & Methods: Personality traits were assessed with the computerized Schedule for Nonadaptive and Adaptive Personality‐2 (SNAP‐2). Results: Cross‐sectionally, we found that participants with BD had elevated Suicide Proneness and Low Self‐esteem versus TDCs at baseline. Furthermore, longitudinal analyses in the BD participants for whom we had 1.5 years of prospectively collected illness‐course data showed that greater Suicide Proneness and Low Self‐esteem prospectively predicted greater levels, shorter time until occurrence, and greater frequency of suicidal ideation during the follow‐up. Conclusion: Our findings suggest the role of specific personality‐related vulnerabilities in the course of BD that, pending replication, could contribute to development of interventions focused on personality traits among individuals with BD.